Health care challenges at mass gatherings - Athanasios Zafeirakis; Panagiotis Efstathiou (National Scientific Medical Center, 2020)
Mass gatherings are unique events carrying the potential to severely strain public health planning and infrastructures by triggering the entire emergency mechanism of a community or nation. That is mostly the case in terrorist attacks, an overwhelming, though not the most common health-related hazard in mass gatherings. The implementation of a protective mechanism against such threats is pronouncedly cumbersome and requires a complex administrative strategy, detailed operational planning and also a deep interoperability of the major health and homeland security stakeholders. That can be accomplished with an Incident Command System that affords organizational guidelines and flexible tactical planning, which refer to actions undertaken before, during and after the incident. The main challenges before the health incident are named preparedness, surveillance, incident action plans, environmental health/food safety and personnel training; the objectives to be achieved during the main phase of the incident are communication, response, dispensing planning and interoperability. Of the post-incident phase, the most important objectives are the mental first aid provision and the transparent key-messages of post hazard communication.